Dampak Islamic Corporate Governance terhadap Keyakinan Muzaki pada Lembaga Amil Zakat - Muhammad Syauqi; Nurul Fitriyah; Jumaati (MALIA: Jurnal Ekonomi Islam, 2022)
This study aims to determine the impactIslamic Corporate Governance on the level of muzaki's trust in the National Amil Zakat Institution (LAZNAS). Quantitative data with a questionnaire of 100 respondents, the sample used is muzaki who tithe at LAZNAS â‰¥3 years (technical purposive sampling). Data analysis techniques using methodsStructural Equation Model (SEM) with modelsPartial Least Square (PLS). The results of the first, third and fourth hypothesis testing are not significant to the level of muzaki's trust in LAZNAS, because of the valuep-value greater than 0.005 and valuet-statistics < 1.96. That means the variables of transparency, responsibility and independence have no effect on the level of muzaki's trust in LAZNAS. While the second, fifth and sixth hypotheses are significant to the level of muzaki's trust in LAZNAS, have valuep-value smaller than 0.005 and valuet-statistics >1.96. It is the variables of accountability, justice andsyariah compliance significantly to the level of muzaki's trust in LAZNAS, the more LAZNAS implements these principles, the more muzaki's trust in LAZNAS. ___________________________________________ Penelitian ini bertujuan mengetahui dampak Islamic Corporate Governance terhadap tingkat kepercayaan muzaki pada Lembaga Amil Zakat Nasional (LAZNAS). Data kuantitatif dengan kuesioner sebanyak 100 responden, sampel yang digunakan muzaki yang berzakat di LAZNAS â‰¥3 tahun (teknik purposive sampling). Teknik analisis data menggunakan metode Structural Equation Model (SEM) dengan model Partial Least Square (PLS). Hasil uji hipotesis pertama, ketiga dan keempat tidak signifikan terhadap tingkat kepercayaan muzaki pada LAZNAS, karena nilai p-value lebih besar dari 0,005 dan nilai t-statistics < 1,96. Itu berarti variabel transparansi, responsibilitas dan independensi tidak memiliki pengaruh terhadap tingkat kepercayaan muzaki pada LAZNAS. Sedangkan hipotesis kedua, kelima dan keenam signifikan terhadap tingkat kepercayaan muzaki pada LAZNAS, memiliki nilai p-value lebih kecil dari 0,005 dan nilai t-statistics > 1,96. Hal ini variabel akuntabilitas, keadilan dan syariah compliance signifikan terhadap tingkat kepercayaan muzaki pada LAZNAS, semakin LAZNAS menerapkan prinsip-prinsip tersebut maka akan meningkatkan kepercayaan muzaki pada LAZNAS.